Improving Dietary Self-Efficacy: A Case Study of the 'Reaksi' Application in a 15-18 Year-Old Adolescent Girl at SMK PGRI 3 Malang - Cahyani, Vionna Fazrin; Suprapti; Yuliawati, Dwi; Hamarno, Rudi (Futurity Medicine, 2025)
Introduction: Dietary self efficacy is crucial for adolescents, directly influencing their ability to adopt healthy eating habits. The "Reaksi" application provides educational resources aimed at improving self-efficacy in this demographic. This case report explores the impact of this application on self-efficacy among a specific group of adolescent girls at SMK PGRI 3 Malang. Case Presentation A total of 69 10th-grade girls were selected through proportional random sampling at SMK PGRI 3 Malang. Data were collected in May 2024 using a validated Self-Efficacy to Regulate Eating Habits Questionnaire. Prior to the intervention, 43% of respondents had low self-efficacy. After using the "Reaksi" app, 67% showed increased dietary self-efficacy. The Wilcoxon test confirmed the results were statistically significant (p < 0.05). Conclusion: The findings indicate that the "Reaksi" app effectively enhances dietary self-efficacy in adolescent girls, demonstrating the potential of technology-based interventions in promoting healthy eating habits.